Cybercrime investigation case studies an excerpt from Placing the suspect behind the keyboard - Shavers, Brett (Syngress, 2013)
Investigative case management is more than just organizing your case files. This title provides you with traditional and innovative methods of data analysis to identify and eliminate suspects through a combination of supporting methods of analysis.